Efektivitas Amelioran pada Lahan Gambut Terdegradasi untuk Meningkatkan Pertumbuhan dan Serapan NPK Tanaman Jagung Manis (Zea mays L. var. saccharata) - Maftu’ah, Eni; Maas, Azwar; Syukur, Abdul; Purwanto, Benito Heru (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
This study was aimed to determine the effectiveness of several of ameliorant formulas to increase plant growthand NPK uptake on sweet corn (Zea mays L. var. saccharata) on degraded peatlands. The research was conducted in thegreenhouse of Balittra during May to July 2011. Sweet corn was planted in pot with soil taken from previously burnt peatin Kalampangan, Palangkaraya. The treatment consisted of two factors, i.e., combination of ameliorant (A1=80% chicken manure + 20% dolomite, A2=80% agricultural weeds + 20% dolomite, A3=80% mineral soil (Spodosol) + 20% dolomite,A4=20% chicken manure + 20% agricultural weeds + 20% Eleocharis dulcis + 20% mineral soil + 20% dolomite, andA5=19% chicken manure + 71.5% mineral soil + 9.5% dolomite) and application rates at 5, 10, 15, 20 and 25 ton ha-1, arranged in a randomized complete block design, with 3 replications. The results showed that ameliorants and application rates affected growth and NPK uptake of sweet corn. Application of 20 ton ameliorant (80% chicken manure + 20% dolomite) ha-1 produced the highest dry weight of root and shoot, and NPK uptake.Keywords: ameliorants, degraded peatland, nitrogen, phosphate, potassium